The Mediating Role of Ambivalence Over Emotional Expression in Explaining the Effect of Cognitive Emotion Regulation Strategies on the Psychological Well-Being of Mothers of Children with Autism - Homeili, Nasrin; Tarimoradi, Arezo; Peyvandi, Parisa; Hosseinzadeh Taghvai, Marjan; Danesh, Esmat (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to examine the mediating role of ambivalence over emotional expression in explaining the effect of cognitive emotion regulation strategies on the psychological well-being of mothers of children with autism. Methodology: This study employed a descriptive correlational design, and structural equation modeling was used for data analysis. The statistical population included all mothers of children with autism in special education schools and rehabilitation centers in Tehran during the 2021–2022 academic year. A total of 300 mothers were selected through convenience sampling and responded to the Ambivalence Over Emotional Expression Questionnaire (AEEQ; King & Emmons, 1990), the Cognitive Emotion Regulation Questionnaire (CERQ; Garnefski & Kraaij, 2006), and the Psychological Well-Being Scale (PWB; Ryff, 1989). The collected data were analyzed using confirmatory factor analysis with AMOS 24 software. Findings: Structural equation modeling results indicated that all goodness-of-fit indices supported an acceptable fit of the structural model with the collected data. Maladaptive emotion regulation strategies negatively and significantly predicted psychological well-being, while adaptive emotion regulation strategies positively and significantly predicted psychological well-being in mothers of children with autism. Ambivalence over emotional expression negatively and significantly predicted psychological well-being in these mothers (p = .001). Moreover, among mothers of children with autism, ambivalence over emotional expression significantly mediated the relationship between emotion regulation strategies and psychological well-being (p = .001). Conclusion: The findings of this study can be useful for counselors, psychologists, and professionals working in the field of autism.